2016
DOI: 10.5897/ajar2015.10526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resettlement on vegetation status and rangeland condition in southwestern Ethiopia

Abstract: This study was conducted with the objectives of comparing range condition of an area under different land use practices (resettled and non-resettled) and assessing the possible effect of resettlement on range condition in Meinit-Shasha district of Bench-Maji zone, southwest Ethiopia. Two kebeles were selected purposively where vegetation and soil conditions were investigated in 40 quadrats across 20 sampling sites using 20 × 20 m (400 m 2 ) quadrat, which was distributed along transects. The investigation incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
4
1
0
Order By: Relevance
“…This may be ascribed to increased human demands for survival leading to over cutting of trees for use in charcoal production, firewood, bricks baking, huts building, thatching and bush clearing for crop production. The study was in agreement with earlier studies which were conducted in Ethiopia by Olson et al (2004), and Berhanu et al (2016).…”
Section: Wetlandsupporting
confidence: 93%
“…This may be ascribed to increased human demands for survival leading to over cutting of trees for use in charcoal production, firewood, bricks baking, huts building, thatching and bush clearing for crop production. The study was in agreement with earlier studies which were conducted in Ethiopia by Olson et al (2004), and Berhanu et al (2016).…”
Section: Wetlandsupporting
confidence: 93%
“…Generally, bare land cover was increased at a rate of 22.3 % annually during the study period ( Table 2). The result of this study is in agreement with the findings of previous studies from arid and semi-arid rangelands (Tegegn et al, 2011;Elias et al, 2015;Yonas et al, 2016), which reported high levels of bare soil in the rangelands.…”
Section: Magnitude Of Lulc Changessupporting
confidence: 83%
“…In general, the woodland cover was decreased at a rate of 33.82% annually during the study period (Table 2). The results of this study are in line with several studies that documented a decline in wood vegetation cover in Ethiopian rangelands (Tsegaye et al, 2010;Belay et al, 2014;Yonas et al, 2016).…”
Section: Magnitude Of Lulc Changessupporting
confidence: 81%
See 2 more Smart Citations